Harnessing a Continuous‐Flow Persulfuric Acid Generator for Direct Oxidative Aldehyde Esterifications. Issue 2 (5th December 2022) - Nagy, Bence S.; Fu, Gang; Hone, Christopher A.; Kappe, C. Oliver; Ötvös, Sándor B.
Abstract: Persulfuric acid is a well‐known oxidant in various industrial‐scale purification procedures. However, due to its tendency toward explosive decomposition, its usefulness in organic synthesis remained largely underexplored. Herein, a continuous in situ persulfuric acid generator was developed and applied for oxidative esterification of aldehydes under flow conditions. Sulfuric acid served as a readily available and benign precursor to form persulfuric acid in situ. By taking advantage of the continuous‐flow generator concept, safety hazards were significantly reduced, whilst a robust and effective approach was ensured for direct transformations of aldehydes to valuable esters. The process proved useful for the transformation of diverse aliphatic as well as aromatic aldehydes, while its preparative capability was verified by the multigram‐scale synthesis of a pharmaceutically relevant key intermediate. The present flow protocol demonstrates the safe, sustainable, and scalable application of persulfuric acid in a manner that would not be amenable to conventional batch processing. Abstract : Acid flow : A continuous‐flow persulfuric acid generator and its application for direct oxidative esterification of a variety of aldehydes is presented herein. By forming the potentially dangerous oxidant in situ, the safety hazards are significantly reduced, and persulfuric acid is successfully utilized as a simple, robust, and easily scalable oxidant within a closed flow reactor environment.